ANALISIS PEMBELAJARAN DARING MENGGUNAKAN BANTUAN MEDIA ELEKTRONIK SELAMA PANDEMI COVID-19 - Muhammad Amanatullah; Arya Setya Nugroho; Nanang Khoirul Umam (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
ABSTRACT The background of this research is the COVID-19 pandemic that hit Indonesia. The world of education has had a huge impact. The government's solution to keep the learning process going is online learning. The purpose of this research is to find out whether online learning can support the learning process at home. So the researchers conducted a study entitled "Electronic Media Assisted Learning in the Conditions of the Covid-19 Pandemic". This type of research is descriptive qualitative. The aim is to describe online learning of Indonesian lessons for the 2020-2021 academic year for the even semester at UPT SDN 34 GRESIK. The research subjects were principals, teachers, and 4th grade elementary school students. The research procedure is to determine the problem, research and conclusions. Data collection techniques through observation, interviews, and questionnaires. Research instruments: 1. Observation, 2. Interview, 3. Questionnaire. Data analysis techniques are reduction, display, and conclusion verification. The results of the observation of the formulation of the problem, namely: Online learning using smartphone, laptop/computer media. The obstacles faced are quotas and signals. While the things that support that is from the school, teachers, parents, and the government. Based on the results of interviews, it is known that online learning is more difficult than face-to-face learning. While the results of the questionnaire most of the respondents liked face-to-face learning. Researchers hope that online learning can run smoothly, with cooperation between teachers, students and parents. Keywords: , ,